The Implicit Religion of Organs: Transformative Experiences, Enduring Connections and Sensuous Nations - MacDonald, Arlene (Implicit religion, 2007)
Religion is not absent from the study of organ transplant. However, it is the formal, explicit components of religion that are attended to. This paper argues the concept of implicit religion more aptly describes and evaluates the language, rituals and symbols that pervade recipient narratives, transplant communities and broader public discourse about organ exchange. Drawing on ethnographic research with transplant recipients and other transplant populations, the paper endeavours to show how this hermeneutic tool illuminates both the individual and collective dimensions of transplant. An implicit religion of organs is evident in the transformations that transplant recipients attest to. An implicit religion of organs also underwrites contemporary understandings of death and immortality. And, finally, an implicit religion of organs is deployed in civil ceremonies designed to solidify, engage and envision the republic.